Lumutinines A−D, linearly fused macroline−macroline and macroline−sarpagine bisindoles from alstonia macrophylla - Kam, T.S.; Lim, S.H.; Tan, S.J.; Low, Y.Y. (American Chemical Society and American Society of Pharmacognosy, 2011)
Four new linearly fused bisindole alkaloids, lumutinines A−D (1−4), were isolated from the stem-bark extract of Alstonia macrophylla. Lumutinines A (1) and B (2) represent the first examples of linear, ring A/F-fused macroline−macroline-type bisindoles, while lumutinines C (3) and D (4) were constituted from the union of macroline and sarpagine moieties. A reinvestigation of the stereochemical assignment of alstoumerine (8) by NMR and X-ray diffraction analyses indicated that the configuration at C-16 and C-19 required revision.